Supply Chain Innovations and Partial Ownership - Matthias Hunold; Shiva Shekhar (Review of Industrial Organization, 2021)
When knowledge sharing is non-contractible, we show that competing downstream firms may prefer to help improve an inefficient alternative supply source than help to improve the technology of the efficient actual supplier—even if this is costless. A downstream firm can have incentives to decrease the efficiency of the actual supplier in order to improve its outside options. Non-controlling partial backward ownership can—through the participation of the downstream firm(s) in the upstream profits—align the incentives of the supplier and its competing customers. This improves industry performance while simultaneously benefiting consumers. Partial backward ownership has similar effects as strengthening a downstream firm's bargaining power and making knowledge sharing contractible.
Keywords: L22; L40; 330; Innovation; Knowledge sharing; Minority shareholdings; Supply chain efficiency; Vertical partial ownership